Sonogram Dinamika Ovarium pada Kambing Kacang (Capra hircus) (SONOGRAM OF OVARIAN DYNAMIC IN KACANG GOAT (CAPRA HIRCUS)) - ., Santoso; ., Amrozi; Purwantara, Bambang; ., Herdis (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
A research was conducted to study the ovarian dynamics in kacang goats. Six non pregnant kacang goatswere used in this research. They were clinically healthy, 2 3 years old and showed normal estrous cycles. Theestrous cycles of the kacang goats were synchronized by using prostaglandin 0.5 mg/kg body weight duringluteal phase. The ovarian dynamics were observed daily by using transrectal ultrasonography. Ovarian dynamicswere characterized by follicular wave. The estrous cycle of kacang goats was 20.0±1.1 days. An ovulatoryfirst follicle wave was appeared on days 1-4, the second follicles wave was on days 3-7, the third folliclewave was on days 8-13, while the ovulatory follicular wave emerged on day 17-18. The dominant folliclesreached the maximum diameter in 3.1±0.6 days from wave emergence and the preovulatory dominantfollicle, the diameter was 6.5±0.5 mm. The corpus luteum of kacang goat was observed on 2.0±0.5 daysafter ovulation up to 2.8±0.8 days before the next ovulation. Follicular development consists of three orfour follicular waves and CL developments were static.
Keywords: corpus luteum, follicle, kacang goat, transrectal ultrasonography